2020
DOI: 10.1021/acs.orglett.0c00728
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of para-Nitrophenyl Glycosides from Reducing Sugars in Water

Abstract: Reducing sugars may be directly converted into the corresponding para-nitrophenyl (pNP) glycosides using 2-chloro-1,3dimethylimidazolinium chloride (DMC), para-nitrophenol, and a suitable base in aqueous solution. The reaction is stereoselective for sugars with either a hydroxyl or an acetamido group at position 2, yielding the 1,2-trans pNP glycosides. A judicious choice of base allows extension to di-and oligosaccharide substrates, including a complex N-glycan oligosaccharide isolated from natural sources, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, the application of glycosyltransferases is still hampered by the high cost of the activated sugars required as glycosylation donors. On the contrary, nitrophenyl-sugars are more cost-effective donors, easier to handle, and synthesize 76 , which implies an advantage of rBxTW1-E495A over glycosyltransferases as a versatile synthetic biotool. The development of strategies of enzyme immobilization and recycling will probably be the next steps to improve the cost-effectiveness of the developed biotool.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of glycosyltransferases is still hampered by the high cost of the activated sugars required as glycosylation donors. On the contrary, nitrophenyl-sugars are more cost-effective donors, easier to handle, and synthesize 76 , which implies an advantage of rBxTW1-E495A over glycosyltransferases as a versatile synthetic biotool. The development of strategies of enzyme immobilization and recycling will probably be the next steps to improve the cost-effectiveness of the developed biotool.…”
Section: Discussionmentioning
confidence: 99%
“…phenols like o-or p-nitrophenol. 42,43 Since hydroxyazobenzenes are more acidic than phenol, we decided to study the DMC-mediated glycosylation reaction of DHABs with unprotected sugars in aqueous solutions (Scheme 1d).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Glycosylation with unprotected sugars in aqueous media is not trivial. , Recently, 2-chloro-1,3-dimethylimidazolinium chloride (DMC) has been successfully used as a dehydrative condensing agent to synthesize 2-pyridyl 1-thioglycosides or phenyl-β- O -glycosides , by a reaction of unprotected sugar with respectively 2-mercaptopyridine or phenol derivatives under basic aqueous conditions . It has been shown that good yields (up to 84%) can be obtained with relatively acidic phenols like o - or p -nitrophenol. , Since hydroxyazobenzenes are more acidic than phenol, we decided to study the DMC-mediated glycosylation reaction of DHABs with unprotected sugars in aqueous solutions (Scheme d).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, an aqueous activation of anomeric hydroxy groups using 2‐chloro‐1,3‐dimethylimidazolinium chloride (DMC) as dehydrating reagent was reported by Shoda and co‐workers. Thus, 1,6‐anhydrosugars, [14] glycosyl oxazolines, [15] glycosyl azides, [16] thioglycosides, [17] and para ‐nitrophenyl glycosides [18] can be synthesized in one step from unprotected sugars in aqueous solutions (Scheme 1b). Recently, Miller and co‐workers [19] reported a site‐selective aqueous glycosylation of unprotected sucrose and analogues using glycosyl fluorides as donors in the presence of calcium ion.…”
Section: Introductionmentioning
confidence: 99%